Decomposition and Nutrient Release of Selected Green Manure Species at Different Stages of Growth on Alisols at Areka, Southern Ethiopia - Habte, Mulugeta; Gebrekidan, Heluf; Haile, Wasie (International Journal of Natural Sciences Research, 2013)
Decline in soil fertility is major constraint to agricultural production and food security in Ethiopian highland farming systems. Since farmers have limited capacity to invest in fertilizers, potential solution to the problem is to use green manure (GM) for their multiple advantages. Thus, this study was conducted to determine optimum time for decomposition and nutrient release from GM at different ages. The treatments were three levels of age (3, 4 and 5) months after planting (MAP), three GM species (Tithoniadiversifolia, Tephrosiavogelii and Crotalaria juncea) and five times of decomposition (7, 14, 21, 28 and 35) days after incorporation (DAI) laid out in Split-split plot design with three replications. Age, species and decomposition time were assigned to the main, sub and sub-sub plots, respectively. The interaction effect of age, species and decomposition time was significant (P < 0.05) on soil pH, OM and NO3–N. During the decomposition process decline in soil pH was observed whereas other parameters increased as decomposition time extended. Organic matter increased from 4.45% (non-treated) to 5.76, 5.40 and 5.96% due to C. juncea, T. diversifolia and T. vogelii, respectively, 28 DAI. On plots treated by C. juncea, soil NO-3-N was increased by 17.60 and 12.10 mg kg-1 compared to the control (11.31 mg kg-1) 35 and 21 DAI, respectively. In plots amended by T. diversifolia and T. vogelii the increment was 33.43 and 24.63 mg kg-1, respectively, 21 DAI compared to the control. Total N, available P and K were significantly (P<0.05) influenced only by time of decomposition. Significantly higher N (1.80 g kg-1) was observed at 28 and 35 DAI whereas higher available K (655.93 mg kg-1) was obtained at 35 DAI.